Cancerous Protein Network That Inhibits the Tumor Suppressor Function of WW Domain-Containing Oxidoreductase (WWOX) by Aberrantly Expressed Molecules - Saigo, Chiemi; Kito, Yusuke; Takeuchi, Tamotsu (Frontiers in Oncology, 2018)
WW domain-containing oxidoreductase (WWOX) is an emerging tumor suppressor protein that contains two N-terminal WW domains and a central short-chain dehydrogenase/reductase domain. WWOX protein plays a part in a signaling network that suppresses carcinogenesis through binding of its first WW domain to various cancer-associated proteins, i.e. p73, AP-2γ, and others. Although the tumor suppressor property of WWOX is inarguable, WWOX is not inactivated in the manner characteristic of the canonical Knudson hypothesis. Impairment of both alleles of WWOX is thought to be a rare event, only occurring in a few cancer cell lines. How is the tumor suppressor function of WWOX impaired in cancer cells? Recent advances highlight that a small transmembrane protein possessing a PPxY motif, called TMEM207, and its relatives are aberrantly expressed in various cancer cells and hinder the tumor suppressor function of WWOX through inhibiting its WW domain. Here, we review the recent findings related to the pathobiological properties of TMEM207 and its relatives based on clinicopathological and experimental pathological studies.